2009
DOI: 10.1038/sj.bjc.6605440
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of endogenous SPARC enhances pancreatic cancer cell growth: modulation by FGFR1-III isoform expression

Abstract: BACKGROUND: Secreted protein acidic and rich in cysteine (SPARC) is a multi-faceted protein-modulating cell -cell and cell -matrix interactions. In cancer, SPARC can be not only associated with a highly aggressive phenotype, but also acts as a tumour suppressor. The aim of this study was to characterise the function of SPARC and its modulation by fibroblast growth factor receptor (FGFR) 1 isoforms in pancreatic ductal adenocarcinoma (PDAC). METHODS AND RESULTS: Exogenous SPARC inhibited growth, movement, and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 21 publications
7
48
0
Order By: Relevance
“…On the other hand, the inactivation of SPARC by aberrant DNA methylation has also been reported in pancreatic, ovarian, colon and lung cancers (9,11,12,22). With regards to SPARC function, exogenous SPARC inhibits the proliferation, movement and migration of human cancer cell lines (11,23), which is consistent with the results of an in vivo study (14). A recent study also provided evidence that exogenous SPARC enhances the apoptosis of colon cancer cells via the caspase 8 pathway (24).…”
Section: B Discussionsupporting
confidence: 79%
“…On the other hand, the inactivation of SPARC by aberrant DNA methylation has also been reported in pancreatic, ovarian, colon and lung cancers (9,11,12,22). With regards to SPARC function, exogenous SPARC inhibits the proliferation, movement and migration of human cancer cell lines (11,23), which is consistent with the results of an in vivo study (14). A recent study also provided evidence that exogenous SPARC enhances the apoptosis of colon cancer cells via the caspase 8 pathway (24).…”
Section: B Discussionsupporting
confidence: 79%
“…There is strong evidence that SPARC is important in the development of pancreatic cancer (15)(16)(17)(18)(19)(20)(21)(22). However, the precise effects of SPARC are cell type dependent, and the effect of SPARC on the growth and survival of islet ␤ cells has not previously been examined.…”
Section: Secreted Protein Acidic and Rich In Cysteine (Sparc)mentioning
confidence: 99%
“…High SPARC expression in the stroma was correlated with a less favorable prognosis [37,38]. Recent data by Mantoni et al [38] and Chen et al [39] have demonstrated that PSCs express higher levels of SPARC than pancreatic cancer cells, and that SPARC could be detected in the conditioned medium of PSCs [39]. However, the precise function of SPARC in PDAC progression remains conjectural.…”
Section: Pscs Promote Tumor Progressionmentioning
confidence: 99%